Detection of Carriers in Glanzmann's Thrombasthenia - Zonneveld, G T E; van Leeuwen, E F; Sturk, A; ten Cate, J W (Thrombosis and Haemostasis, 1983)
Quantitative glycoprotein (GP) analysis of whole platelets or platelet membranes was performed by SDS-polyacrylamide gelelectrophoresis (SDS-PAGE) and periodic acid Schiff staining in the families of two unrelated Glanzmann’s thrombasthenia (GT) patients. Each family consisted of two symptom free parents, a symptom free daughter and a GT daughter. All symptom free members had a normal bleeding time, clot retraction and platelet aggregation response to adenosine 5’-diphosphate (ADP), collagen and adrenalin. Platelet Zw* antigen was normally expressed in these subjects. GT patiens, classified as a type I and II subject, showed reduced amounts of GP lib and of GP nia. Analysis of isolated membranes in the non-reduced state, however, showed that the amount of GP Ilia was also reduced in three of the four parents, whereas one parent (of the GT type I patient) and the two unaffected daughters had normal amounts of GP Ilia. Quantitative SDS-PAGE may therefore provide a method for the detection of asymptomatic carriers in GT type I and II.
Keywords: Glanzmann’s thrombasthenia; Carrier detection; Quantitative SDS-polyacrylamide gel electrophoresis; Platelet membrane glycoproteins